Diversity of flea beetles from the Nanling Mountains, China, with description of three new species of Minota Kutschera (Coleoptera: Chrysomelidae) - Zhang, Meng-Na; Ruan, Yong-Ying; Liang, Zu-Long; Yang, Xing-Ke; Chen, Xiao-Qin; Peng, Ying-Ying; Xie, Qi; Meng, Zi-Ye (Zootaxa, 2024)
The Nanling Mountains is one of the sixteen biodiversity hotspots in China. It divides the central and southern regions of the country. This paper documents the diversity of flea beetles in the Nanling Mountains based on a comprehensive insect biodiversity survey from 2020 to 2022. Three new species of the genus Minota Kutschera, 1859 viz. M. cuiae Zhang, Ruan, Liang & Yang sp. nov. (Guangxi), M. maoer Zhang, Ruan, Liang & Yang sp. nov. (Guangxi), and M. bimaculata Zhang, Ruan, Liang & Yang sp. nov. (Jiangxi) from the Nanling Mountains are described and illustrated. A checklist and key to the Chinese Minota species are provided.